Pengembangan Sumber Daya Manusia Dan Penempatan Kerja Terhadap Kepuasan Kerja Karyawan (Studi Empiris Pada PT Marga Maju Mapan Cabang Divisi Proyek Bekasi) - Lulu Gita; R. Deni Muhammad Danial; Nor Norisanti (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the magnitude of the influence of human resource development and job placement on job satisfaction of employees of PT Marga Maju Mapan Bekasi Project Division Branch. The method used in this research is descriptive and associative research with a quantitative approach. The sampling technique in this study used saturated sampling, the samples taken in this study were 38 employees. The data analysis technique used validity and reliability tests, multiple linear regression including correlation coefficients, determination, research model testing and research hypothesis testing. The results of the study using the coefficient of determination (R2) showed that the development of human resources and work placement on employee job satisfaction was 67.4% while the remaining 32.6% was influenced by other factors outside of this study. Based on the multiple correlation coefficient test, it can be seen from the R value of 0.674 which means that there is a very strong relationship between human resource development and job placement on employee job satisfaction. The results of the F test, namely the value of Fcount 14,584>3,26 indicates that Fcount is greater than Ftable. The variables of human resource development and work placement have a positive and significant effect on employee job satisfaction. Keywords: Human Resource Development, Job Placement, Employee Job Satisfaction